The Influence of Emotional Experiences and Behavioral Intentions of Tourists through Destination Image and Satisfaction - Paskalis Dakhi; Martaleni Martaleni; Dwi Orbaningsih; Umi Muawanah (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines how emotional experiences influence the behavioral intentions of international tourists visiting, with destination image and satisfaction as mediating variables. The study aims to explain the psychological mechanisms through which tourism experiences are translated into revisit intention and recommendation behavior. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) based on data collected from 165 international tourists. The findings indicate that emotional experiences significantly affect destination image, satisfaction, and behavioral intentions. Destination image and satisfaction also have significant effects on behavioral intentions and function as mediating variables in the relationship between emotional experiences and behavioral intentions. Satisfaction emerges as the strongest predictor of behavioral intentions, indicating that evaluative judgments play a crucial role in shaping loyalty-related behavior. The discussion highlights that tourist behavior is influenced by the interaction among affective, cognitive, and evaluative processes, in which emotional experiences shape perceptions, and satisfaction strengthens behavioral outcomes. These findings contribute to tourism behavior literature, particularly in adventure-based destinations, by emphasizing the importance of emotionally engaging experiences in strengthening destination image, satisfaction, and long-term tourist loyalty.